Kiyai Muhammad Jeddawi Sang “Singa Jambi” Di Era 1960-1980-An - A. Muthalib (Jurnal Edukasi, 2022)
In the past, in the territory of Tahtul Yaman along the city of Jambi, Jambi Province, there was one of the Kyai Pondok who was called by the community "Jambi Lion," because his horned behavior was similar to that of Umar bin Khaththab, the second Prophet, as it is known that Umar ben Khatthhab was called "Sand Lion" because of his brave attitude, both to friends and opponents, but his attitude was only against "a person or group of people who violated the rules of Allah Ta'ala. It's like gambling and drinking, and that's whatKyaiMuhammadJeddawidid.In this study, the author uses the basis of the historical method, that is, through four stages: heuristics, criticism, interpretation, and historiography (penulisan). While his theory is qualitative theory, library research, and interviews, Kyai Jeddawi has a brave, firm, and intelligent attitude. That's why the title was embedded in Kyai Jeddawi. However, it is worth noting that the attitude shown by Kyai is focused only on matters related to Allah’s Shariah when among his people who deliberately violate Like the boys who are drunk in the middle of the highway and the women who are in the midst of the road, so is Kyai Jeddawi acting. Besides, he never interfered with the activities of society, but "it is society itselfthatsometimesknowsitself."If you look further, the presence of a figure like Kyai Jeddawi is very much needed by the Muslims of this era because his attitude is much more helpful to society than the "action of the police." Therefore, Jambi feels that since the death of Kyai Jeddawi in 1988, they have lost a figure such as Kyai.